Big five personality traits, gaming motives, and regular and disordered gaming: A cross-national examination among college student gamers in seven countries - López Fernández, Francisco (2024)
Introduction. Previous research has shown that personality traits and gaming motives are important predictors for explaining regular and disordered gaming. However, the mediating role of gaming motives in the relation between personality traits and video game outcomes (e.g., time spent gaming or disordered gaming) has been scarcely studied and limited cross-national studies have addressed this issue. The present study aimed to examine the direct and indirect effects of the Big Five personality traits on weekly gaming and disordered gaming via gaming motives across seven countries. Method. 3540 college student gamers (59.5% women) from the U.S., Canada, Spain, Argentina, Uruguay, South Africa and England completed the online survey. Structural equation modeling was conducted to test models. Multigroup models were employed to test model invariance across countries. Results. Significant, albeit weak, relations were found between personality traits and gaming outcomes, and were mediated mostly by coping motives in predicting disordered gaming, and by social interaction and recreation (to a lesser extent) motives in predicting weekly gaming. Some minor, yet significant, differences across countries appeared and are discussed in detail. Discussion. The present findings indicate that the differential interrelations between personality traits, gaming motives, and video gaming outcomes may be generalized in college students across countries.